Teaching the distinctive language of science: An integrated and scaffolded approach for pre-service teachers. (July 2017) - Feez, Susan; Quinn, Frances
Abstract: To learn science and demonstrate science learning, school students must bridge the gap between everyday use of language and image and the specialised use of language and image needed to achieve science curriculum outcomes. Pre-service teachers studying at a regional Australian university were shown how to help their future students bridge this gap. A transdisciplinary model was used to demonstrate the teaching of specialised science literacies integrated with the teaching of science in the middle school years, resulting in high levels of engagement, more effective use of learning time, and valuable opportunities for teacher educator professional learning. Highlights: Science knowledge and the language of science. Integrating science education with literacies education in initial teacher education. Using genre-based literacy pedagogy to teach science writing in the middle years.